ANALISIS INVESTASI DI INDONESIA PERIODE 2001-2010 - B01108120, Fitria Elvi (Jurnal Pembangunan dan Pemerataan, 2013)
The study is titled analasis of investment the Indonesia during 2001-2010, the goal is to determine how much influence the variables GDP, inflation and interest rates on investment and to see the level of elasticity to investment in Indonesia during the period 2001-2010. The analysis used multiple regression analysis on the multiple use to see the relationship between the variables GDP, inflation and interest rates to invest in Indonesia. The data used are secondary data (quarterly period of 2001 -2010 4th quarter - 1st quarter) of the Central Statistics Agency (BPS)and Bank Indonesia (BI). The results showed that the Gross Domestic Product (GDP), and the investment credit interest rates have a significant effect on the amount of investment in Indonesia. Unless inflation is no significant effect on investment in Indonesia. Based on the test results of elasticity, the Gross Domestic Product (GDP) and the investment credit interest rate is elastic, while inflation is inelastic. Keywords : Investment, Gross Domestic Product (GDP), Inflation, Interest Rate Investment